Association of corrected QT interval with body mass index, and the impact of this association on mortality: Results from the Third National Health and Nutrition Examination Survey. Issue 4 (July 2017) - Waheed, Salman; Dawn, Buddhadeb; Gupta, Kamal
Summary: Background: Both QT interval and body mass index (BMI) are independently associated with mortality. Those with higher BMI have longer QT, although evidence is inconsistent. The joint association of QT and BMI with mortality merits investigation. Objective: To examine the association of QT with BMI, and to examine the joint association of QT and BMI with all-cause and cardiovascular mortality. Methods: We followed 4036 participants from NHANES III for a median of 14.7 years. Weighted sample was divided into 4 categories by BMI as: 18.5–24.9, 25–29.9, 30–34.9 and ≥35, and 2 categories by corrected QT interval (QTc) as: normal (<450 ms in males, <460 ms in females) or prolonged. Cox proportional hazards models were used with adjustment for demographic characteristics and cardiovascular risk factors. Results: QTc was longer among those with higher BMI (mean QTc: 424.7, 425.8, 430.9 and 437.8 respectively for BMI 18.5–24.9, 25–29.9, 30–34.9 and ≥35, p-trend: <0.001). Overall, longer QTc or higher BMI were associated with increased all-cause and cardiovascular mortality risk compared to mean QTc or mean BMI, respectively. When combined, cardiovascular mortality was significantly increased among obese individuals with prolonged QTc [hazard ratio (95% CI): 3.1 (1.2–8.0) and 4.8 (1.2–19.9) but not when QTc was normal [1.0 (0.5–2.0) and 1.4 (0.8–2.8)] for BMI 30–34.9 and ≥35, respectively compared to BMI 18.5–24.9 and normal QTc. Similar (although not statistically significant) findings were observed for all-cause mortality. Risk prediction for both all-cause and cardiovascular mortality improved when QTc was added to the adjusted model with BMI (net reclassification index 0.14, p = 0.01 and 0.14, p < 0.0001 for all-cause and cardiovascular mortality, respectively). Conclusion: Individuals with higher BMI have a significantly longer QTc. BMI is associated with increased all-cause and cardiovascular mortality risk when QTc is prolonged but not when QTc is normal. These novel observations suggest that QTc should be factored into risk stratification of obese individuals with a screening electrocardiogram. This may help stratify individuals into lower risk categories when QTc is normal.